(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the poetic evolution of the ode genre in Russian literature from the second half of the 18th century to the 20th century. It explores how the genre, initially formed within the framework of classicism, gradually acquired humanistic, philosophical, and lyrical features. The article highlights the contribution of poets such as G.R. Derzhavin and A.S. Pushkin, who transformed the ode into a vehicle for expressing personal and moral ideas. Additionally, the study examines the modernization of the genre in the 20th century by poets like V. Mayakovsky and A. Voznesensky, who introduced irony, political pathos, and journalistic tone into their odes. The work also addresses genre transformation, including the blending of ode with other poetic forms such as essay and publicist poetry. Overall, the article demonstrates that the ode genre, although rooted in tradition, remained dynamic and continued to evolve in response to socio-political changes and aesthetic demands.